2017
DOI: 10.1177/1747493017743801
|View full text |Cite
|
Sign up to set email alerts
|

Canadian stroke best practice consensus statement: Secondary stroke prevention during pregnancy

Abstract: The Canadian Stroke Best Practice Consensus Statement: Secondary Stroke Prevention during Pregnancy, is the first of a two-part series devoted to stroke in pregnancy. This document focuses on unique aspects of secondary stroke prevention in a woman with a prior history of stroke or transient ischemic attack who is, or is planning to become, pregnant. Although stroke is relatively rare in this cohort, several aspects of pregnancy can increase stroke risk during or immediately after pregnancy. The rationale for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 59 publications
1
55
0
Order By: Relevance
“…Refer to Secondary Prevention of Stroke during Pregnancy module for detailed information on stroke prevention management and pharmacotherapy. 7 Poststroke antenatal obstetric considerations for women with a stroke in pregnancy…”
Section: Early Poststroke Management In a Pregnant Womanmentioning
confidence: 99%
“…Refer to Secondary Prevention of Stroke during Pregnancy module for detailed information on stroke prevention management and pharmacotherapy. 7 Poststroke antenatal obstetric considerations for women with a stroke in pregnancy…”
Section: Early Poststroke Management In a Pregnant Womanmentioning
confidence: 99%
“…We were surprised that this patient had not previously undergone a medical or neurologic assessment for her history of presumed transient ischemic attacks. According to the recent guidelines, prepregnancy counseling and secondary stroke prevention could have been valuable in this case [11]. Furthermore, although several studies have reported the characteristics of pregnancyrelated stroke, information on rehabilitation strategies for stroke during pregnancy is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…In Canada, ~62,000 people are treated for stroke and transient ischemic attack. In a series of publications, the Heart and Stroke Foundation Canadian Best Practice Committees have been developing various evidence-based recommendations to address issues regarding: telestroke technologies ( 95 ); managing transitions of care following stroke ( 96 ); mood, cognition, and fatigue following stroke ( 97 ); hyperacute stroke care ( 98 ); secondary prevention of stroke ( 99 ); and stroke during pregnancy ( 100 , 101 ).…”
Section: Methodsmentioning
confidence: 99%